PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN SABUN LUX PADA KONSUMEN MINIMARKET ATHA MART DI KOTA PALEMBANG - Roma Dona; Erwita Gratika; Zubaidah Warni (Jurnal Manajemen, 2020)
The purchase decision making process is a process that starts from the introduction of problems that can be solved through the purchase of several products. This study aims to determine the effect of product quality, price and television advertisements on Lux Soap purchase decisions on Atha Mart Minimarket consumers in Palembang. The population in this study are all consumers who buy Lux Soap in the Atha Mart Minimarket, and the sample is part of the population. The sampling technique is the Accidental Sampling technique, data analysis using validity, reliability, classic assumption test, multiple regression analysis, t test and F test. The results showed that the quality of the product had a positive and significant effect of 0.297, the price had a positive and significant effect amounted to 0.185 and television advertisements had a positive and significant effect of 0.360 on the decision to purchase the Lux Atha Mart minimarket consumer soap in Palembang. From the results of the determination test that product quality, price, and television advertising influence the decision to purchase Lux soap in Atha Mart minimarket consumers by 57% and the remaining 43% is influenced by other variables.